(untitled) (Journal of Educational Sciences, 2025)
The article discusses ways to assess and improve the level of ethical use of artificial intelligence by future teachers through training. The purpose of the study is to determine the level of education of future teachers in the ethical and safe use of artificial intelligence, as well as to suggest ways to develop it through the introduction of special training modules.The study was conducted in three stages. At the first stage, methods and tools for assessing the level of compliance with ethical standards when using artificial intelligence were substantiated. At the second stage, the level of compliance of future teachers with ethical requirements in the process of using artificial intelligence technologies is determined. At the third stage, the structure and content of the training was developed, aimed at developing the skills of ethical interaction with artificial intelligence among the participants of the experiment. The assessment criteria were based on the levels of understanding, application and creation presented in the Framework of Competencies in the field of artificial intelligence for Students proposed by UNESCO. The main research methods used were questionnaires, a self-assessment scale, and formative learning. The respondents’ responses were evaluated on the Likert scale, and statistical data processing was carried out using the P.V. Sysoeva method. The practical part of the study involved 32 students of pedagogical specializations from Abai Myrzakhmetov Kokshetau University.The results showed that despite the active use of artificial intelligence tools by the participants, their understanding of ethical standards remains insufficient. Based on this, a structure of the training content for future teachers was proposed, aimed at developing ethical responsibility, honesty and fairness in accordance with the principles of FATE (Fairness, Accountability, Transparency, Ethics). Keywords: artificial intelligence, generative artificial intelligence, ethical and safe use, future teacher, assessment of the level of ethics, application and creation.